Knowledge and attitudes on organ donation among final year undergraduate medical students in Universiti Malaya / Daniel Chow Ren Kiat - Daniel Chow , Ren Kiat (2018)
Organ donation is a noble act, and the demand for it is not met enough globally. Malaysia alarmingly has one of the lowest organ donation rates, and this might be due to a lack of awareness and knowledge among Malaysians, including health care providers and medical students. Objective: This study was conducted to ascertain the rate of organ donor pledgers, to assess the knowledge and attitudes, and to investigate the relationship between various socio-demographic factors with the knowledge and attitudes of organ donation among final year undergraduate medical students in Universiti Malaya. Methods: This observational analytical cross-sectional study was carried out by using the questionnaire method. The questionnaire included three sections (Socio-demographic data, Knowledge and Attitude). SPSS was utilized to analyze the collected data. Chisquare and independent t-test were used for inferential statistics. The socio-demographic data was then compared with the knowledge, willingness and attitude in which ANOVA (analysis of variance) was performed. Results: 116 medical students participated in this study. 61.2% of them had good organ donation knowledge while 63.8% of students were willing to register for organ donation. However, only 13.8% were organ donation pledgers. There was a significant association found between the knowledge score and the willingness to become an organ pledger (p=0.009). Students with good knowledge (67.6%) were more willing to become an organ pledger. In terms of religion, Buddhists were more likely to have positive attitude on organ donation when compared to Muslims. Conclusion: The percentage of organ donation pledgers among medical students is higher when compared to the general population in Malaysia. Generally, medical students iv possess good knowledge on organ donation, but aggressive awareness programs with a more structured curriculum can improve this further, as better knowledge leads to more positive attitude towards organ donation, and ultimately, the willingness to pledge. Keywords : Organ Donation, awareness, attitude, knowledge